Analisis Perbandingan Biaya Pembangunan Jembatan Menggunakan Konstruksi Konvensional dan Pre-cast ( Study Kasus TOL SUMATERA, Paket 4, Jalur 8 Ruas Bandar Jaya ) - zulkarnain, Aditya; Hadi, Martono; Diana, I Wayan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
Bridges are one of the most important means of transportation for humans. In the construction of bridge construction, there are 2 methods used namely conventional and pre-cast methods. Both of these methods have differences in the construction of the upper building structure alone. In the pre-cast bridge construction: When the work for the upper structure of the building is 59 days, the number of workers is 130 people, the work barriers are not too constraining the traffic. Whereas in conventional bridge construction: The work time is 110 days, the number of workers is 104, the obstacle of work will hamper the traffic below. From the analysis of the two types of bridges, pre-cast bridges are 20% more expensive than conventional bridges, but the pre-cast bridge work time is 51 days faster.Keywords : Pre-cast bridge construction, Conventional bridge construction .